AT EXCHANGE PROCESS IN ROTARY REGENERATIVE AIR PRE–HEATER - Abdulla A. Azamov; Mansur A. Bekimov (Ural Mathematical Journal)
A simplified mathematical model of a rotary regenerative air pre–heater (RRAP) is suggested and studied based on the averaged dynamics of the heat exchange process between nozzles and a heat carrier (i.e. air or gas–smoke mixture). Averaging in both spatial coordinates and time gives a linear discrete system that allows deriving explicit formulas for determining the characteristics of the air heater and establishing some properties such as periodicity, stability, ergodicity and others.